CoII, NiII and UO2II complexes with β-diketones and their arylhydrazone derivatives: Synthesis, structure and catalytic activity in Henry reaction. (24th November 2015) - Ma, Zhen; Sutradhar, Manas; Gurbanov, Atash V.; Maharramov, Abel M.; Aliyeva, Rafiga A.; Aliyeva, Farqana S.; Bahmanova, Fidan N.; Mardanova, Vusala I.; Chyragov, Famil M.; Mahmudov, Kamran T.
Graphical abstract: Co II, Ni II and UO2 II complexes with β-diketones and their arylhydrazone derivatives effectively and diastereoselectively catalyze the Henry reaction. Abstract: The new uranyl, nickel and cobalt complexes, [UO2 (L 1 )2 (R)] (1 ), [Ni(L 1 )2 ((CH3 )2 SO)2 ] (2 ), [Co(H2 O)4 (HL 2 )2 ]·2H2 O (3 ) and [UO2 (H2 O)2 (HL 2 )2 ]·2H2 O (4 ), were prepared by reaction of UO2 (CH3 COO)2 ·2H2 O, Ni(CH3 COO)2 ·4H2 O or Co(CH3 COO)2 ·4H2 O with 1, 3-diphenyl-propane-1, 3-dione (H2 L 1 ) or 4-(2-(2, 4-dioxopentan-3-ylidene)hydrazinyl)benzoic acid (H2 L 2 ) in the presence of N, N-diethylnicotinamide (R) (for1 ). Complexes1 –4 were characterized by elemental analysis, IR spectroscopy, ESI-MS and single crystal X-ray diffraction technique. In both1 and2 the (L 1 ) − coordinates in a bidentate chelating mode where the UO2 2+ in1 exhibits a distorted pentagonal bipyramidal and Ni 2+ in2 a distorted octahedral geometries. In3 and4 a hydrazone moiety containing an intramolecular resonance assisted hydrogen bond, with N–H⋯O distances of 2.5469(18) and 2.549(7) Å, respectively, was found in the coordinated ligand (HL 2 ) − . The supramolecular networks (packing diagrams) of1 –4 are constructed via hydrogen bonding, CH–π or π–π interactions. All the four complexes (1 –4 ) act as a good catalyst towards the diastereoselective nitroaldol (Henry) reaction of aliphatic and aromatic aldehydes with nitroethane in different solvents such as acetonitrile, methanol or water. Complex3 was found to be efficient catalyst for the Henry reaction in aqueous medium, providing β-nitroalcohols with good yields (68–91%) and diastereoselectivities ( syn / anti 77:23–73:27).